The stellar Populations of E and SO galaxies as seen with SAURON - Kuntschner, H; Emsellem, E; Bacon, R; Bureau, M; Cappellari, M; Davies, R; de Zeeuw, T; Falcon-Barroso, J; Krajnovic, D; McDermid, R; Peletier, R; Serzi, M (2007)
We present selected results from integral-field spectroscopy of 48 early-type galaxies observed as part of the SAURON survey. Maps of the H beta, Fe5015, Mgb and Fe5270 indices in the Lick/IDS system were derived for each of the survey galaxies. The metal line strength maps show generally negative gradients with increasing radius roughly consistent, with the morphology of the light profiles. Remarkable deviations from this general trend exist, particularly the Mg b isoindex contours appear to be flatter than the isophotes of the surface brightness for about 40% of our galaxies without significant dust features. Generally these galaxies exhibit significant rotation. We infer from this that the fast-rotating component features a higher metallicity and/or an increased Mg/Fe ratio, as compared to the galaxy as a whole.We also use the line strength maps to compute average values integrated over circular apertures of one effective radius, and derive luminosity weighted ages and metallicities. The lenticular galaxies show a, wide range in age and metallicity estimates, while elliptical galaxies tend to occupy regions of older stellar populations.